Blue and red light photoluminescence emission at room temperature from CaTiO3 decorated with α-Ag2WO4 - Mondego, Mayara; de Oliveira, Regiane C.; Penha, Maya; Li, Máximo Siu [UNESP]; Longo, Elson (Elsevier, 2017)
CaTiO3 (CT) and α-Ag2WO4 (AW) semiconductors are widely known for their interesting electrical and photoluminescence (PL) properties. In this study, we decorated CT with AW for obtaining CaTiO3:α-Ag2WO4 (CT:AW), and investigated the properties of the produced materials, especially their PL properties. The X-ray diffraction peaks of the synthesized microcrystals were well indexed to the orthorhombic phase for all the samples. Two morphologies: cube-like for CT and rod-like for AW were observed by field-emission scanning electron microscopy (FE-SEM). The FE-SEM and transmission electron microscopy (TEM) studies indicated the presence of rod-shaped AW deposited on the surfaces of cube-shaped CT morphology. PL emission of the decorated samples overlaps all the visible region spectra because of the contribution from both the constituent materials that induce maximum emissions in the blue and red regions. The examination of Commission internationale de ĺéclairage (CIE) coordinates confirmed that the decorated samples exhibit favored emission the red wavelength region.
Keywords: Calcium titanate; Decoration; Optical properties; Silver tungstate